„Trianon teóriájánál... rosszabb Trianon praxisa" : a békediktátum tizedik évfordulójára - 1930 - Vizi, László Tamás (Közép-Európai Közlemények, 2013)
On the first round anniversary of the Treaty of Trianon, in 1930, both in Budapest and in the countryside massive protest rallies, marches, demonstrations were held. Similar events took place in most of the foreign countries where Hungarians live. The rally in Budapest was organized by the Hungarian Revisionist League and the Social Association to the Liberty Square. In front of a crowd Tianon as the darkest misdeed of the history. On the 4th June 1930, the Hungarian National Assembly held a grief session. Before agenda, the highly respected former head of the Hungarian peace delegation of 1920, earl Albert Apponyi spoke and explained the Hungarian nation’s resolution against Trianon. Apponyi in his major speech gived Trianon’s and relentless criticism and showed that Trianon reported only a formally peace. In reality, it was an unilaterally dictate, forced to the Hungarians. After Apponyi, the social democrat István Farkas criticized Trianon from the right of peoples to self-determination. The study analyzes the speeches told on the rally of Budapest and the National Assembly and presents both the domestic and foreign protests against Trianon. The latter is described based on Lord Rothermere's article published in the Daily Mail.